(3GdeYbHI aj GdUaGJs - (3GHf GUHZ , eMeO Hf YjSi Hf eMeO Hf GUHZ Hf GdefGUa GdGROj, CHh YHO Gddg,J (B620 (3g` s ((3CHh LYaQ CMeO Hf EHQGgje Hf CMeO GdSdei s)
(3ChdgG (B:s
(3bGd GdTjN CHh YHO Gddg eMeO Hf YjSi GdMeO ddg hMb GdMejO dg hGdNdb hGdCeQ hMce GdeYOdI s
(3BNQgG (B:s
(3hGdMeO ddg aGdGMJTGe dMeOg hGdHOA hGdJeGe hGdMeO ddg dg GdEOZGe CaVd eG jMeOg GdCfGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdfSNI HgG MhGTs
(3ai MhGTjgG TQhM hJYdjbGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B322 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B107s
Keywords: (3GddZIs